2018
DOI: 10.1016/j.cell.2018.06.021
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Architecture of the Mouse Nervous System

Abstract: SummaryThe mammalian nervous system executes complex behaviors controlled by specialized, precisely positioned, and interacting cell types. Here, we used RNA sequencing of half a million single cells to create a detailed census of cell types in the mouse nervous system. We mapped cell types spatially and derived a hierarchical, data-driven taxonomy. Neurons were the most diverse and were grouped by developmental anatomical units and by the expression of neurotransmitters and neuropeptides. Neuronal diversity w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

196
2,763
11
11

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 2,299 publications
(2,981 citation statements)
references
References 50 publications
196
2,763
11
11
Order By: Relevance
“…As BAC-transgene expression is sometimes ectopic relative to endogenous gene expression, we also assessed expression of endogenous Agtr1a and found that 97 ± 2% of Hsd11b2 -expressing neurons also contain mRNA for Agtr1a, the angiotensin II receptor (Figure 4P-R). In contrast, mRNA for angiotensinogen ( Agt , the precursor for angiotensin peptides), though abundant in the dorsal vagal complex, co-localizes exclusively with the astrocytic gene Apoe , never Hsd11b2 or Phox2b (not shown), consistent with evidence that brain Agt expression is astrocyte-specific (Stornetta et al, 1988; Zeisel et al, 2018). …”
Section: Resultssupporting
confidence: 63%
“…As BAC-transgene expression is sometimes ectopic relative to endogenous gene expression, we also assessed expression of endogenous Agtr1a and found that 97 ± 2% of Hsd11b2 -expressing neurons also contain mRNA for Agtr1a, the angiotensin II receptor (Figure 4P-R). In contrast, mRNA for angiotensinogen ( Agt , the precursor for angiotensin peptides), though abundant in the dorsal vagal complex, co-localizes exclusively with the astrocytic gene Apoe , never Hsd11b2 or Phox2b (not shown), consistent with evidence that brain Agt expression is astrocyte-specific (Stornetta et al, 1988; Zeisel et al, 2018). …”
Section: Resultssupporting
confidence: 63%
“…A recent analysis of pericyte-deficient Pdgfb ret/ret mice shows a defective development and persistence of glymphatic function, suggesting that PDGFB signaling plays an important role in the development of the glymphatic system [62]. Cells with a transcriptome profile closely resembling the perivascular brain fibroblast have been observed in other transcriptomic analyses of brain cells [2,6] and additional, but not yet fully characterized, fibroblast subtypes have been identified [2,17], indicating a broader fibroblast landscape within and around the CNS. However, it should be kept in mind that the development of the vasculature in the Pdgfb ret/ret mice is more generally altered, including capillary dilation and impaired BBB function [20].…”
Section: Paravascular Flowmentioning
confidence: 99%
“…Thus, more than 500 molecularly distinct classes of neurons and glial cells have been identified in the mouse brain [1,2], and information about the cellular composition of specific brain regions is increasing rapidly [2][3][4][5][6][7][8]. In addition, there is an even larger number of supporting glial cells, i.e., astrocytes and oligodendrocytes, the latter forming myelin sheets around neurons and making up a large part of the white matter in the brain.…”
Section: Introductionmentioning
confidence: 99%
“…38 This demonstrated that human peripheral (tibial-mixed motor and sensory) nerve is among the tissues with the highest expression of PDXK (Fig 2A), with evidence for expression specifically in peripheral sensory neurons, based on single cell mouse transcriptomic data (see Fig 2B). 38 This showed different co-expression profiles in brain compared to peripheral nerve tissue. Weighted gene co-expression analysis demonstrated that in 9 of 11 brain regions analyzed, PDXK was coexpressed with genes relating to synaptic transmission and neuronal identity, whereas co-expression data from the tibial nerve showed that PDXK was located within a module enriched for genes involved in oxidation-reduction processes (GO: 055114; false discovery rate-corrected p = 2.36 × 10 −9 ; see Fig 2C and Supplementary Table 3).…”
Section: Identification Of Disease-causing Pdxk Variantsmentioning
confidence: 87%